2020
DOI: 10.1371/journal.pone.0227234
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence of Bartonella, Babesia, and hemotropic Mycoplasma species in dogs with hemangiosarcoma from across the United States

Abstract: Hemangiosarcoma (HSA), a locally invasive and highly metastatic endothelial cell neoplasm, accounts for two-thirds of all cardiac and splenic neoplasms in dogs. Bartonella spp. infection has been reported in association with neoplastic and non-neoplastic vasoproliferative lesions in animals and humans. The objective of this study was to determine the prevalence of Bartonella spp. in conjunction with two other hemotropic pathogens, Babesia spp. and hemotropic Mycoplasma spp., in tissues and blood samples from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…A recent study reported an association between Bartonella spp and canine hemangiosarcoma. 38 Ten of 24 dogs tested in our study had detectable Bartonella spp sequences, although these were present in low abundance ( Table S3 ). Furthermore, four of the samples contained only sequences from B. bacilliformis, B. grahamii, or B. tribocorum, which infect humans and rats, respectively, and none of which is known to infect dogs as a primary or accidental host.…”
Section: Resultsmentioning
confidence: 86%
“…A recent study reported an association between Bartonella spp and canine hemangiosarcoma. 38 Ten of 24 dogs tested in our study had detectable Bartonella spp sequences, although these were present in low abundance ( Table S3 ). Furthermore, four of the samples contained only sequences from B. bacilliformis, B. grahamii, or B. tribocorum, which infect humans and rats, respectively, and none of which is known to infect dogs as a primary or accidental host.…”
Section: Resultsmentioning
confidence: 86%
“…Downregulation of ILF2 expression levels has been shown to inhibit cell proliferation [ 37 ], whereas downregulation of IFL3 expression, in addition to inhibition of cell proliferation, also inhibits cell migration and invasion and promotes cell apoptosis [ 38 ]. Some parasites such as Babesia , Plasmodium and Leishmania can cause unlimited cell proliferation after infecting hosts to eventually cause diseases in hosts [ 39 , 40 ]. This study showed that after B. microti infection in mice, the expression levels of ILF2 and IFL3 in the spleen were downregulated; notably, the expression levels were downregulated to the lowest levels at 11 days.…”
Section: Discussionmentioning
confidence: 99%
“…antigens was less than 3% in 15,451 diagnostic sera submitted by veterinarians suspecting infection with a vector-borne pathogen further supports IFA specificity when testing dogs [ 30 ]. Regrettably, Bartonella IFA sensitivity is poor when testing dogs with PCR-confirmed infections [ 41 , 42 ]. Thus, epidemiological studies using dog sera should have excellent specificity, but will underestimate exposure among dogs regionally.…”
Section: Discussionmentioning
confidence: 99%